Evaluation of user experience in the operation of electric vehicles in the Arctic regions - Shvetsov Alexey; Shvetsova Svetlana; Gromov Viktor (E3S Web of Conferences)
The availability of electric vehicle (EV) technology for users in various regions of the planet has increased significantly in recent years due to the reduction of their cost and the development of service infrastructure. Electric vehicles have traditionally focused on operation in temperate and warm climates, but gradually they are also beginning to be used in the northern and Arctic regions of the planet with a cold climate. One of the main keys to the success of electric vehicle technology in the northern and Arctic regions is an understanding of the user experience (UE) that arises in drivers when using EVs in the special climatic conditions of such regions. This article presents the results of an experimental assessment of UE users of battery electric vehicles in the northern and Arctic regions on the example of one of the largest Arctic regions of the planet – the Republic of Sakha (Yakutia).